Penerapan Material Batu Alam Berdasarkan Sifat dan Karakteristiknya pada Bangunan Masjid Ar-Rayyan Kementerian BUMN - Hisyam Nafhan Fadilah; Bambang Subekti (Universitas Indraprasta PGRI, 2023)
The existence of proper and comfortable worship facilities in the office environment is an important factor in supporting the spiritual needs of every employee who works, this has prompted the Ministry of BUMN to renovate the Ar-Rayyan Mosque building. This study aims to analyze the application of natural stone types according to their functions in a building so that they can be taken into consideration in choosing building materials, especially natural stone. The results showed that the application of different types of natural stone in the Ar-Rayyan Mosque building had their respective functions and purposes, while their placement in the building depended on the motifs that were adapted to the design concept and the nature of each type of natural stone. Natural stone is a material suitable for use as building skin because in addition to its natural motifs and patterns, natural stone makes it look good in design and can also be used as natural insulation in buildings.